Shoah in Marian Pankowski’s Literary Art - Morawiec, Arkadiusz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The article centers on the theme of the Holocaust in the literary works of Marian Pankowski: its sources, relations with the concentration camp theme, particular works and their poetics, as well as the aesthetic, social and political problems related to the theme of the Holocaust.